2015
DOI: 10.1002/pssa.201532203
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of carbon nanoparticle–solvent molecule interactions in Raman and fluorescence spectra

Abstract: Phone: þ7 495 939 16 53, Fax: þ7 495 939 11 04Interactions of oxidized detonation nanodiamond and carbon dots with protic solvent molecules in suspensions of water, methanol, and isopropyl alcohol were studied by Raman and fluorescence spectroscopy. The structure of the solvent at the interface with nanoparticles and the strength of the hydrogen bonds between the functional groups on the surface of the nanoparticles and the solvent molecules depend on the type of solvent. The molecules of the solvent affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…For a quantitative description of the fluorescence of ND in suspensions, parameter F 0 was used. It is the ratio of the integral intensity of fluorescence and integral intensity of the water Raman valence band .…”
Section: Resultsmentioning
confidence: 99%
“…For a quantitative description of the fluorescence of ND in suspensions, parameter F 0 was used. It is the ratio of the integral intensity of fluorescence and integral intensity of the water Raman valence band .…”
Section: Resultsmentioning
confidence: 99%
“…Such electronic transitions can affect the optical, colloidal, and chemical properties of DND in water. The influence of the surrounding solvent molecules on the fluorescence properties of dispersed DND was demonstrated by Dolenko and Burikov et al . There was observed a dependence of the fluorescence intensity of dispersed DND on the amount and strength of hydrogen bonds in water and in protic solvents.…”
Section: Introductionmentioning
confidence: 88%
“…Currently, there are many literature data on essential interactions between the ND surface and the surrounding molecules of the solvents, in particular, of water . Chakrapani et al have demonstrated that in an aqueous suspension of the hydrogenated detonation nanodiamonds (DND) occurs regular exchange of electrons between the hydrogen on the surface of ND and water molecules, resulting in absorption or formation of molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…The authors convincingly showed that detonation NDs (DNDs) dispersed in water and other protic solvents significantly affect the structure of the surrounding layers of solvents, including changing the strength of hydrogen bonds in suspensions. According to the results of the authors, a stable water shell with a thickness of about 0.5 nm is formed in the water around NDs, and the properties of the shell differ significantly from those of bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alterations of hydrogen bonds are so great that the electronic structure of water in the ND shell is comparable with the structure of high‐density amorphous ice. According to the results of a study of NDs aqueous suspensions, dispersed NDs weaken hydrogen bonds in bulk water, and the change of the hydrogen bonds energy mainly depends on the type of surface functional groups of the nanoparticles. With the help of Fourier‐transform infrared spectroscopy, Raman spectroscopy, and X‐ray absorption spectroscopy of aqueous suspensions of DNDs with different surface functional groups—carboxyl (DND–COOH), hydroxyl (DND–OH), hydrogenated (DND–H), and a polyfunctional surface (DND–poly)—authors obtained a series on the degree of influence of DNDs with different functionalization of the surface on the forces of hydrogen bonds in water: DND–H >> DND–OH > DND–poly > DND–COOH > water.…”
Section: Introductionmentioning
confidence: 99%